Analisis Tingkat Kepatuhan Minum Obat pada Pasien Diabetes Melitus Tipe 2 di RST dr. Soedjono Magelang - Rahmadani, Azmi; Nuraini, Siti; Sukmawati, Ari (Indonesian Journal of Medical and Pharmaceutical Science, 2024)
Background: Diabetes mellitus is a chronic disease that requires long-term and complex treatment, where one of the determinants of successful therapy depends on drug compliance. The purpose of this study was to determine the characteristics of patients including gender, age, education level, duration of illness, comorbidities on the level of drug compliance in type 2 diabetes mellitus patients. Method: This type of research is descriptive research with a cross-sectional approach. Data collection using the Morisky Medication Adherence Scale-8 (MMAS-8) questionnaire to see the level of compliance in Diabetes Mellitus patients. Results: The level of drug compliance in type II diabetes mellitus patients at RST TK II dr. Soedono Magelang is low compliance 29 patients (34.25%), moderate compliance 34 patients (42.5%) and high compliance 17 patients (21.25%). Conclusion: There is a significant relationship between age, education status, duration of suffering and also comorbidities with drug compliance in type 2 Diabetes Mellitus patients at RST dr. Soedjono Magelang.